Evaluation of Bisphenol A influence on endocannabinoid system in pregnant women. (July 2018) - Zbucka-Kretowska, Monika; Zbucki, Robert; Parfieniuk, Ewa; Maslyk, Maciej; Lazarek, Urszula; Miltyk, Wojciech; Czerniecki, Jan; Wolczynski, Slawomir; Kretowski, Adam; Ciborowski, Michal
Abstract: Bisphenol A (BPA) is a synthetic chemical widely used in the industry, which may potentially evoke negative effects on human health, especially on reproductive processes and fetal development. BPA has been reported to act on estrogen, estrogen-related, androgen, thyroid hormone, pregnane X, peroxisome proliferation-activated, and aryl hydrocarbon receptors. However, other potential mechanisms of BPA action on pregnancy cannot be excluded. Comprehensive evaluation of BPA effect on pregnant women can be performed by use of metabolomics. In the present study LC-MS-based plasma metabolomics was performed in the group of pregnant women with known concentrations of free, conjugated and total BPA. Significant positive correlations were observed between several endocannabinoids (fatty acid amides) and free (r = 0.307–0.557, p-value = 0.05–0.00002) and total (r = 0.413–0.519, p-value = 0.008–0.00006) BPA concentrations. Palmitoleamide was positively correlated with conjugated (r = 0.348, p-value = 0.05) while lysophosphatidylethanolamine 18:0 with free (r = 0.519, p-value = 0.00006) BPA concentration. The docking calculations of BPA and fatty acid amide hydrolase (enzyme degrading endocannabinoids, FAAH) indicated that it can act as a competitive inhibitor by blocking FAAH catalytic residues. In vitro study showed that BPA moderately inhibits FAAH activity (15% decrease for 200 ng mL-1 and almost 50% for 200 μg mL-1 of BPA). In the present study for the first time inhibitory potential of BPA on FAAH hydrolase is reported. Inhibition of FAAH may lead to a rise of plasma endocannabinoids level. BPA exposure and increased level of endocannabinoids are miscarriage risk factors. Based on obtained results it can be hypothesized that BPA may induce adverse pregnancy outcomes by acting on endocannabinoid system. Highlights: BPA may affect plasma metabolome of pregnant women. Plasma levels of BPA and endocannabinoids are positively correlated. BPA may inhibit fatty acid amide hydrolase. BPA may induce adverse pregnancy outcomes by acting on endocannabinoid system.